Heterosis and combining ability for leaf yield and its components in vegetable amaranth (Amaranth us tricolor) - REDDY, V V PRATAP; VARALAKSHMI, B (The Indian Journal of Agricultural Sciences, 2013)
Heterosis, general and specific combining ability variances and their effects were studied for nine characters in line x tester design in vegetable amaranth (Amaranthus tricolor L.). The results indicated the pre-dominance of non-additive gene action for plant height, leaf number, leaflength, leaf breadth, stem girth, stem weight, leaf weight and plant weight. Additive gene action was preponderant for leaf stem ratio. Significant heterosis over both the better and mid-parents was expressed by ’AV 22’ X ’AV 69’ for plant height, ’AV 6’ x ’AV 69’ for plant weight. The best combiners were ’AV 6’, ’AV 22’ among the 5 lines and ’AV 69’ of the 2 testers. Based on both the specific combining ability effects and mean performance, cross’ AV 31’ x ’AV 69’ was found to be superior for plant yield and its attributes, viz leaf breadth, stem girth, stem weight and leaf weight.